Efektifitas Skala Edinburgh dan Skala Beck dalam Mendeteksi Risiko Depresi Post Partum di Rumah Sakit Umum Prof. DR. Margono Soekarjo Purwokerto - Latifah, Lutfatul; Hartati, (Jurusan Keperawatan FIKES UNSOED, 2006)
The aim of this study is to evaluate the effectiveness of Edinburgh post partum depression scale (EPDS) and Beck Depression Inventory (BDI) scale to detect risk of post partum depression. This study utilized survey with quantitative approach. Of 25 patients were chosen with purposive sampling method. The criteria of sample was post partum mother who admitted at Margono Soekardjo hospital in the sixth days. The assessment of post partum mother was evaluated directly to the target population by EPDS and BDI scale. The criteria of depression were divided into three categories, low risk, middle risk and high risk of post partum depression. Mann-Whitney U shows that EPDS and BDI scale have similar effective to detect risk of post partum depression at 0.01 with Z value at (2.33) and (-2.320) respectively. In summary, the effectiveness of EPDS and BDI scale were not different in predicting post partum depression mother during admitted in the hospital. Both of those scales have similar ability when detecting risk of post partum depression mother.